2019
DOI: 10.11591/ijere.v8i4.20340
|View full text |Cite
|
Sign up to set email alerts
|

Academic resilience as mediator of multidimensional perfectionism and academic performance among gen-Z undergraduate students

Abstract: <span>This study focused on the relationship of </span><span lang="IN">two</span><span> dimensions of perfectionism (perfectionistic strivings, and perfectionistic concerns) and academic performance, with the role of academic resilience as mediator. Participants including 132 undergraduate students form age range 18 to 25, from first year to fifth year in their studies mainly from a Malaysian psychology undergraduate program were asked to fill questionnaires containing measures fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
18
0
2
Order By: Relevance
“…There are research findings on the mediating role of academic resilience (e.g. Choo & Prihadi, 2019) and resilience (e.g. Tugade & Fredrickson, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are research findings on the mediating role of academic resilience (e.g. Choo & Prihadi, 2019) and resilience (e.g. Tugade & Fredrickson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Academic resilience has been considered as a mediating variable in many conceptual relationships. For instance, Choo & Prihadi (2019) found that academic resilience plays a mediating role in the relationship between multidimensional perfectionism and academic performance. Secer & Ulas (2020) found that academic resilience has a mediating role in the relationship between anxiety sensitivity, social and adaptive functioning, school refusal, and school attachment.…”
Section: Academic Resilience As a Mediator In Relationship Between Social-emotional Learning Competencies And Life Satisfactionmentioning
confidence: 99%
“…Academically resilient students tend to express higher levels of achievement despite current academic challenges (Ahmed, et al, 2018). Individuals with lower academic endurance are reluctant to make efforts in the face of stress, to regulate goals, compared to individuals with high academic resilience (Choo & Prihadi, 2019). On the other hand, academically resilient students can successfully overcome stressful conditions related to school.…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is defined as an individual's ability to succeed in adapting to adversities or distractions or stress, be able to build clear and realistic goals, relate well and be comfortable with others and be able to solve problems experienced [9]- [13]. This explanation shows that resilience is not only related to an individual's ability to bounce back after experiencing adversity through adaptation, but also to be able to solve problems and establish clear goals.…”
Section: Introductionmentioning
confidence: 99%
“…This explanation shows that resilience is not only related to an individual's ability to bounce back after experiencing adversity through adaptation, but also to be able to solve problems and establish clear goals. Meanwhile, in academics, resilience is defined as an individual's ability to withstand Int J Eval & Res Educ ISSN: 2252-8822  Prevalence of academic resilience of social science students in facing the … (Indriyana Rachmawati) 677 difficult life events, rise and be able to overcome adversity and adapt positively to academic demands [13]- [17]. Thus, academic resilience can be interpreted as an individual's ability to bounce back, find solutions and goals and adapt and feel comfortable with academic demands and other academic difficulties.…”
Section: Introductionmentioning
confidence: 99%